Frolic and detour - Muldoon, Paul 1951- (Farrar, Straus and Giroux, 2019)
"Though Frolic and Detour is Paul Muldoon's thirteenth collection, it shows all the energy and ambition we might generally associate with a first book. Here, the poet brings his characteristic humor and humanity to the chickadee, the house wren, the deaths of Leonard Cohen and C. K. Williams, the Irish Rising, the Great War, and how "a streak of ragwort / may yet shine / as an off-the-record / remark becomes the party line." Frolic and Detour reminds us that the sidelong glance is the sweetest, the tangential approach the most telling, and shows us why Paul Muldoon was described by Nick Laird, writing in The New York Review of Books, as "the most formally ambitious and technically innovative of modern poets, [who] writes poems like no one else.""--
"Originally published in 2019 by Faber & Faber Limited, Great Britain"--Title page verso
Keywords: Irish poetry / 21st century; English poetry / Irish authors; 1900-1999; Poetry